Guidelines for Preventing and Solving Corruption Problems in the Public Sector in a Concrete Way Roi Et Province: Guidelines for Preventing and Solving Corruption Problems in the Public Sector in a Concrete Way Roi Et Province - Barisri, Jirapon; Paladech, Janrob; Muriganon, Phongpun (RATANABUTH JOURNAL, 2025)
Research article on guidelines for preventing and solving corruption problems in the public sector in a concrete way. Roi Et Province have a purpose to create concrete guidelines for preventing and solving corruption problems in the public sector. Roi Et Province It is qualitative research. Important informant Is involved in the prevention and resolution of corruption problems. A total of 35 people were purposively selected. The instrument was an in-depth interview. In collecting data, the data were then analyzed, summarized and the results discussed descriptively. The results showed that Model guidelines for preventing and solving corruption problems in the public sector in a concrete way Roi Et Province consists of 1. opportunities and incentives Awareness should be created with the aim of developing civil servants at all levels to have morality and ethics. in every sector of the agency 2. State administration There should be legislation and guidelines for various operations. that is strict and clear, there will be no gaps in the use of administrative power that can cause corruption, and 3. personal values It should strengthen the creation of values in working that adhere to the moral system rather than the patronage system.